A Strategic Financial Management Approach For Revitalizing Rural Banks: A Literature Review With Prism Approach - Agung, Aria Lutfi (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
This study aims to systematically analyze financial management strategies that can improve the performance and sustainability of Rural Banks (BPRs) in Indonesia. With a focus on liquidity management, capital optimization, economic-social-environmental risk management, and technology integration, this review identifies financial practices that are effective in facing challenges in the rural banking sector. A literature review was conducted using the PRISMA method, resulting in 11 relevant articles. Results show that technology adoption and strategic collaboration can strengthen the competitiveness of BPRs, especially in financial inclusion in the regions. In addition, improved governance and economic-social-environmental risk management play an important role in the sustainability of BPRs.